Using grounded theory approach to identify value-based factors in software development - Zakaria, Noor Azura; Ibrahim, Suhaimi; Mahrin, Mohd Nazri (2017)
Grounded theory is an approach that can be used to analyse qualitative data. It is a systematic approach for data collection, handling and analysis. The objective of this paper is to present adapted grounded theory approach as data analysis strategy to identify value-based factors in software development. The grounded theory procedure started with data extraction and initial coding, memo writing and constant comparative analysis and finally identification of core categories and writing memos. Initial data extracted were 74 which were obtained from 28 sources generally related with software development. After constant comparison and memoing, the valid data (value-based factors) were reduced to 33 with six core categories (classification of value-based factors).